2017
DOI: 10.1186/s12974-017-0819-4
|View full text |Cite
|
Sign up to set email alerts
|

Microglial-derived microparticles mediate neuroinflammation after traumatic brain injury

Abstract: BackgroundLocal and systemic inflammatory responses are initiated early after traumatic brain injury (TBI), and may play a key role in the secondary injury processes resulting in neuronal loss and neurological deficits. However, the mechanisms responsible for the rapid expansion of neuroinflammation and its long-term progression have yet to be elucidated. Here, we investigate the role of microparticles (MP), a member of the extracellular vesicle family, in the exchange of pro-inflammatory molecules between bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
223
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(228 citation statements)
references
References 65 publications
(75 reference statements)
5
223
0
Order By: Relevance
“…Pro-coagulatory molecules and microparticles loaded with TF and phosphatidylserine derived from microglia and astrocytes can activate platelets and induce a hypercoagulatory state or even a consumptive coagulopathy 126,127 . Similarly, pro-inflammatory molecules in microglia-derived microparticles can add to the inflammatory response 128 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…Pro-coagulatory molecules and microparticles loaded with TF and phosphatidylserine derived from microglia and astrocytes can activate platelets and induce a hypercoagulatory state or even a consumptive coagulopathy 126,127 . Similarly, pro-inflammatory molecules in microglia-derived microparticles can add to the inflammatory response 128 .…”
Section: Cerebral and Extracerebral Challenges To The Innate Immune Smentioning
confidence: 99%
“…The presence of EVs in cerebrospinal fluid (CSF) underscores their relevance in neural tissue . In the injured CNS, EVs were recently found to cross the blood–brain barrier and promote neuroinflammation . Furthermore, certain types of EVs appear to support neuronal survival under conditions of ischemic stress .…”
Section: Introductionmentioning
confidence: 99%
“…Microglial activation within the injured area is observed within 6-48 hours post injury [99] but evidence has shown that microglia can maintain a primed or pro-inflammatory profile for weeks to months after the acute effects of injury have dissipated [106]. Recently, it was shown that extracellular vesicles may exchange pro-inflammatory molecules between brain immune cells, as well as to the systemic circulation, as pathways of inflammation propagation following TBI [107].…”
Section: Mechanisms Of Neural Injury In the Traumatic Penumbramentioning
confidence: 99%
“…Previous studies indicated that MSCs promised to be an effective therapy for brain injury in TBI [175-177, 215, 231-236]. Instead of brain remodeling and functional recovery by cell replacement effects, evidence suggests that the major effects of neurorestoration were due to the paracrine effects of secretion-based factors such as MSCs-derived exosomes that may reduce neuroinflammation, promote neurogenesis and angiogenesis, rescue pattern separation and spatial learning impairments, and improve functional recovery after TBI in animal models [107,176,178,191,204,205,215,216,[235][236][237]. In addition, as exosomes contain various miRNAs, which play a key role in modifying the phenotype and/or the physiology and modulating the cellular processes of the recipient cell, and miRNAs such as miR-21 could be potential therapeutic targets for interventions after TBI, the combination of miRNAs and MSC-derived exosomes might be a novel approach for the treatment of TBI [238].…”
Section: Extracellular Vesicles and Exosomesmentioning
confidence: 99%
See 1 more Smart Citation